Managing Sentosa as an attraction for both tourists and local residents. - Chua, Matthew Han Ming. (2008)
Our objective and motivation underlying this research is to contribute in enabling Sentosa achieve its vision of making Sentosa the favorite recreational playground for both locals and tourists. Our results are based on 258 questionnaires completed in different parts of Singapore which form a non-probability sample. All the theoretical frameworks and research methodology are highlighted in Chapter One of the report.